PENINGKATAN HASIL BELAJAR IPA TENTANG MATERI FOTOSINTESIS KELAS V MELALUI MODEL DISCOVERY LEARNING - Charirotud Dina Tsania; Siti Patonah; Suharno (STKIP Subang, 2024)
This research aims to analyze the application of the discovery learning model to photosynthesis material for class V elementary school. This research uses the pre-experiment method, one group pretest posttest. Research is carried out by analyzing problems, then continuing by comparing using learning methods. Data collection in this research used searching from several relevant journals. Data analysis was carried out by means of pretest posttest. The results of the analysis show that the lowest score in the test was 55, the posttest was 56 and the highest score in the pretest activity was 85, posttest 100, in the KKM 75. From this research it can be concluded that learning activities have increased student learning outcomes in learning class V photosynthesis material using the discovery learning model learning.